Design and Development of the Android-Based ‘Desa Bersinar Banyumas’ Application - Salsabilla, Hanin; Usman, Muhammad Lulu Latif (Yayasan Kita Menulis, 2024)
Narcotics are natural, synthetic, or semi-synthetic substances that produce hallucinations and are addictive. Drug abuse can have a negative effect on the user's psyche and also death. BNN implements the Drug Clean Village or Desa Bersinar program to create a drug-free environment. Volunteers or officers collect data on drug users manually by filling in data into a form. In collecting data on drug users, volunteers or BNN officers cannot synchronize data so data collection is prone to duplicate data. The application of computer technology to the Android application can be used as a solution to overcoming the problem of data collection on narcotics users in the Bersinar Village area. The application created with an Android-based application can be used anytime and anywhere. The purpose of this research is to make the Desa Bersinar (Drug Clean) application to record Android-based narcotics users and to conduct testing on the Desa Bersinar application. The research method used in making the Desa Bersinar application is to use the Agile Development System method. The Agile method consists of several stages, namely plan, design, develop, test, deploy, review, and maintenance. From the results of this study it is a Bersinar Village application will be produced that can help volunteers or BNN officers in Banyumas Regency in recording narcotics users in Bersinar Village.